Obshchestvennoe mnenie . Obshchestvennoe mnenie . Public Opinion . Общественное мнение - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A banquet in the State Kremlin Palace, celebrating the elections into the Federal Assembly of the Russian Federation. Contributors: Proshutinskaia, Kira Aleksandrovna (Anchor); Litvinova, Renata Muratovna (Anchor) Банкет в Государственном Кремлевском дворце, приуроченный к выборам в Федеральное собрание Российской Федерации. Создатели: Прошутинская, Кира Александровна (Ведущий/Ведущая); Литвинова, Рената Муратовна (Ведущий/Ведущая)